Synthesis and structure of new 1,2,3-triazolyl substituted 1,3,5-triazines - Mikhaylichenko, Svetlana; Veloso, Anthony; Patel, Kunjal; Zaplishny, Vladimir (European Journal of Chemistry, 2012)
The reaction between monoazido derivatives of 1,3,5-triazine and CH-active carbonyl compounds were studied in order to obtain novel coupled heterocyclic systems with potential bioactivity. Reaction conditions were varied and optimized, a series 2,4-disubstituted derivatives of 6-(1H-1,2,3-triazol-1-yl)-1,3,5-triazines were obtained with good yield.